(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Biotechnological means are under active development, and those related to the use of stem cells, biopolymer-based matrices and their combinations are especially important in the field of medicine. We believe that especially promising is the local use of patient’s autologous biological materials that may significantly enhance the repair processes at the site of damage, with no risk of infection, immunological conflict, and uncontrolled biological degradation, and no ethical problems. This is applied as a universal approach in many fields of medical practice. The potential of patient’s biological materials in neurology (especially, neuroophhthalmology) is under active research. Studies have shown that platelet rich plasma (PRP) and cell-free and stem- and progenitor-cell rich PRP matrices can stimulate neural repair, preventing the loss of optic nerve functions. Particularly, PRP-derived autologous materials, when used in retinal neuronal and optic nerve lesions of various origins, stimulate regenerative processes, with the preservation of neural cell viability, resistance to toxic exposure, and improvement in vascularization. The use of stem and progenitor cells incorporated into the matrix significantly expands it repair potential due to the direct differentiation of these cells, replacement of damaged and lost cells and release of a variety of biologically active substances directly at the site of lesion. Therefore, the data presented in this review demonstrate the viability of the use of autologous biological materials in current neuroophthalmology and the need for developing treatment protocols for particular diagnoses.